Water, oceanic fracture zones and the lubrication of subducting plate boundaries—insights from seismicity. Issue 3 (8th January 2016) - Schlaphorst, David; Kendall, J-Michael; Collier, Jenny S.; Verdon, James P.; Blundy, Jon; Baptie, Brian; Latchman, Joan L.; Massin, Frederic; Bouin, Marie-Paule
Abstract: We investigate the relationship between subduction processes and related seismicity for the Lesser Antilles Arc using the Gutenberg–Richter law. This power law describes the earthquake-magnitude distribution, with the gradient of the cumulative magnitude distribution being commonly known as the b -value. The Lesser Antilles Arc was chosen because of its along-strike variability in sediment subduction and the transition from subduction to strike-slip movement towards its northern and southern ends. The data are derived from the seismicity catalogues from the Seismic Research Centre of The University of the West Indies and the Observatoires Volcanologiques et Sismologiques of the Institut de Physique du Globe de Paris and consist of subcrustal events primarily from the slab interface. The b -value is found using a Kolmogorov–Smirnov test for a maximum-likelihood straight line-fitting routine. We investigate spatial variations in b -values using a grid-search with circular cells as well as an along-arc projection. Tests with different algorithms and the two independent earthquake cataloges provide confidence in the robustness of our results. We observe a strong spatial variability of the b -value that cannot be explained by the uncertainties. Rather than obtaining a simple north–south b -value distribution suggestive of the dominant control on earthquake triggering being water released from the sedimentary cover on the incoming American Plates, or a b -value distribution that correlates with on the obliquity of subduction, we obtain a series of discrete, high b -value 'bull's-eyes' along strike. These bull's-eyes, which indicate stress release through a higher fraction of small earthquakes, coincide with the locations of known incoming oceanic fracture zones on the American Plates. We interpret the results in terms of water being delivered to the Lesser Antilles subduction zone in the vicinity of fracture zones providing lubrication and thus changing the character of the related seismicity. Our results suggest serpentinization around mid-ocean ridge transform faults, which go on to become fracture zones on the incoming plate, plays a significant role in the delivery of water into the mantle at subduction zones.